How do you integrate int4x(x^2+3)^(-3) dx? Calculus Introduction to Integration Definite and indefinite integrals 1 Answer Sasha P. Oct 18, 2015 -1/(x^2+3)^2 + C Explanation: int4x(x^2+3)^(-3) dx = 2 int (x^2+3)^(-3) 2xdx = = 2 int (x^2+3)^(-3) (x^2+3)'dx = 2 int (x^2+3)^(-3) d(x^2+3) = = 2 (x^2+3)^-2/-2 +C = -1/(x^2+3)^2 + C Answer link Related questions What is the difference between definite and indefinite integrals? What is the integral of ln(7x)? Is f(x)=x^3 the only possible antiderivative of f(x)=3x^2? If not, why not? How do you find the integral of x^2-6x+5 from the interval [0,3]? What is a double integral? What is an iterated integral? How do you evaluate the integral 1/(sqrt(49-x^2)) from 0 to 7sqrt(3/2)? How do you integrate f(x)=intsin(e^t)dt between 4 to x^2? How do you determine the indefinite integrals? How do you integrate x^2sqrt(x^(4)+5)? See all questions in Definite and indefinite integrals Impact of this question 1881 views around the world You can reuse this answer Creative Commons License